Diagnostic and Prognostic Significance of Exosomes and Their Components in Patients With Cancers - Zinnat Ara Moni; Zahid Hasan; Md. Shaheen Alam; Nitai Roy; Farhadul Islam (Cancer Medicine)
ABSTRACT Background Cancer is the second leading cause of human mortality worldwide. Extracellular vesicles (EVs) from liquid biopsy samples are used in early cancer detection, characterization, and surveillance. Exosomes are a subset of EVs produced by all cells and present in all body fluids. They play an important role in the development of cancer because they are active transporters capable of carrying the contents of any type of cell. The objective of this review was to provide a brief overview of the clinical implication of exosomes or exosomal components in cancer diagnosis and prognosis. Methods An extensive review of the current literature of exosomes and their components in cancer diagnosis and prognosis were carried out in the current study. Results Tumor cells release exosomes that contribute to the formation of the pre‐metastatic microenvironment, angiogenesis, invasion, and treatment resistance. On the contrary, tumor cells release more exosomes than normal cells, and these tumor‐specific exosomes can carry the genomic and proteomic signature contents of the tumor cells, which can act as tools for the diagnosis and prognosis of patients with cancers. Conclusion This information may help clinicians to improve the management of cancer patients in clinical settings in the future.